2013
DOI: 10.1111/bjh.12234
|View full text |Cite
|
Sign up to set email alerts
|

Parasite maturation and host serum iron influence the labile iron pool of erythrocyte stagePlasmodium falciparum

Abstract: Summary Iron is a critical and tightly regulated nutrient for both the malaria parasite and its human host. The importance of the relationship between host iron and the parasite has been underscored recently by studies showing that host iron supplementation may increase the risk of falciparum malaria. It is unclear what host iron sources the parasite is able to access. We developed a flow cytometry-based method for measuring the labile iron pool (LIP) of parasitized erythrocytes using the nucleic acid dye STYO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…It has been suggested that parasite growth is inhibited during IDA due to an additional reduction in the bioavailability of iron (46). While it remains unclear where and how the parasite obtains the iron necessary for growth, evidence suggests that the parasite meets some of its need by importing iron from serum (16,47,48). Reduced serum iron in individuals with IDA may reduce the parasite's access to iron, thereby inhibiting growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that parasite growth is inhibited during IDA due to an additional reduction in the bioavailability of iron (46). While it remains unclear where and how the parasite obtains the iron necessary for growth, evidence suggests that the parasite meets some of its need by importing iron from serum (16,47,48). Reduced serum iron in individuals with IDA may reduce the parasite's access to iron, thereby inhibiting growth.…”
Section: Discussionmentioning
confidence: 99%
“…In liver-stage infection, reduced iron bioavailability brought on by previously established bloodstage infection inhibits the development of sporozoites, thereby preventing compound infections (15). It has been speculated that an excess of iron bioavailability resulting from iron supplementation may subvert these processes and encourage parasite growth (16,17). Expression of the iron-regulatory protein lipocalin 2 (LCN2) is increased during malaria infection (18), and studies of knockout mice indicate a key role for LCN2 in modulating the innate and adaptive immune responses to infection through its influence on iron recycling (19).…”
mentioning
confidence: 99%
“…Recent work confirmed that infected RBCs contain a larger labile iron pool than uninfected RBCs and showed that this pool increases during asexual development [19]. Surprisingly, the source of the parasite iron is still unclear.…”
Section: The Art Activator: What Is It and Where Does It Come From?mentioning
confidence: 97%
“…citrate, albumin). Because iron binds to these ligands with less affinity than to transferrin, NTBI may be more available to circulating parasites than transferrin‐bound iron (Clark et al , 2013). This line of evidence would suggest that women in the second half of pregnancy are at increased risk compared to their pre‐pregnancy state or in the first half of pregnancy, because iron absorption and thus, the possible production of NTBI due to iron supplementation may be more pronounced in individuals with iron deficiency than in those who are iron replete (Brittenham et al , 2014).…”
Section: Safety Of Antenatal Iron Interventions In Malaria‐endemic Sementioning
confidence: 99%